THE EFFECTIVENESS OF CANVA AS A DIGITAL TOOL IN IMPROVING STUDENTS’ DESCRIPTIVE WRITING SKILLS - Hanifa Maudy Nursyahida; Naf'an Tarihoran; Kheryadi Kheryadi (Universitas Wiralodra, 2026)
This study focuses on the use of Canva as a digital learning tool to improve the skills of junior high school students in descriptive writing. Lack of motivation, practice, and tradition-based teaching methods are some of the reasons why many students find it hard to write. To solve the problems, Canva was integrated into the lesson writing to improve the interest, creativity, and contextual knowledge of students. In his writing theory, Weigle selected a quantitative, quasi-experimental design with a population of 64 7th-grade students in SMPN 1 Cikulur, divided into experimental and control groups. SPSS 25 was used to analyze data (pre-tests, post-tests, and questionnaires). It was found that the experimental group scored higher on the post-test (mean 70.62) than the control group (mean 61.78), and the t-test was significant to prove the improvement (t = 5.552 > 1.67, p < 0.05). Moreover, students interviewed mentioned that Canva had good experiences that made writing both more interesting and creative, though they were affected by poor internet connection. In general, the results imply Canva is a helpful tool to enhance descriptive writing and suggest its incorporation into the process of teaching writing to EFL learners to improve their results.